The validity and reliability of the My Jump 2 application for trained junior and adult athletes (Science & Sports, 2024)
Objectives To examine the reliability, validity, and usefulness of the My Jump 2 application compared to an infrared platform photoelectric cell system in young and adult professional athletes.